An Investigation of Topography Effects on Seismic Ground Motions - Thăng, Nguyễn Công; Nguyên, Phạm Đình (Vietnam Journal of Earth Sciences, 2012)
The paper mentioned the influence of topography of the free surface to seismic ground motions, an important topic in the field of enginerring seismology, but often overlooked in seismic hazard assessments in Vietnam. The paper also introduced a method for estimating these effects in Vietnam context that the distribution of the seismic stations is sparse and the seismic activity is not so high. It is a method to allow simulating seismic wave propagations in three-dimensional media using numerical calculations in unstructured meshes. The method was then applied to investigate the changes of a simple seismic wave field generated by a plane P wave when changing the topography model of the free surface in a systematic way. The main goal of the study was to show effects of topography on seismic ground motions, and initially set up the basis for future assessments of such topography effects at specific locations in Vietnam to serve anti-seismic designs. The obtained results show that topography condition of the free surface is an important factor affecting the seismic wave field. A certain topography leads to an increase of amplitudes of seismic signals for horizontal components at sites around mountain summits. Such influences increase or decrease correspondingly with the increase or decrease of the contrast of the free surface topography.